Early Echocardiographic Predictors of Eventual Need for Patent Ductus Arteriosus Treatment: A Retrospective Study - Koo, Jenny; Torres, Nohemi; Katheria, Anup (American Journal of Perinatology, 2024)
Objective Hemodynamically significant patent ductus arteriosus (hsPDA) in preterm neonates is associated with end-organ injury including intraventricular hemorrhage. Early treatment may reduce morbidities but may result in overtreatment. This study aimed to examine the association between commonly obtained echocardiographic markers within the first 12 hours of life and eventual treatment of an hsPDA.Study Design Patients with <32 weeks' gestational age had blinded echocardiograms done within the first 12 hours of life as part of research protocols. Subsequent treatment of the patent ductus arteriosus (PDA) was determined by the clinical team independent of echocardiogram results. t-tests and chi-square tests were done for continuous data and categorical outcomes. A receiver operating curve was created to optimize cutoff values.Results Among 199 neonates studied (mean time of echocardiogram 6.7 h after birth), those needing PDA treatment had higher left ventricular output (LVO), right ventricular output (RVO), and superior vena cava (SVC) flow (p-values 0.007, 0.044, and 0.012, respectively). Cutoffs for predicting PDA treatment were LVO > 204 mL/kg/min (63% sensitivity, 66% specificity), RVO > 221 mL/kg/min or SVC flow > 99 mL/kg/min (sensitivities 70 and 43%, specificities 48 and 73%, respectively).Conclusion Preterm neonates with higher markers of cardiac output in the first 12 hours of birth later required PDA treatment. These data are the first to use standard cardiac output measures in the first 12 hours of life to predict the need for future PDA treatment. Further prospective studies will need to be performed to corroborate these associations between echocardiographic markers and clinical outcomes/morbidities.Key Points
Keywords: neonatology; hemodynamics; preterm neonates; cardiac output; pulmonary hemorrhage; intraventricular hemorrhage